Procedures 99 - Springhouse Corporation (Springhouse, Pennsylvania : Springhouse Corporation, 1999)
A comprehensive program offering clear, concise, directions on 500 nursing procedures. Each procedure details complete instructions including the equipment needed, preparation of equipment implementation, special considerations, complications and documentation tips
The first and only complete CD-ROM on nursing
System requirements : IBM pc or compatible, Windows 95 or higher, Pentium 90 or higher and 16 MB RAM or more, 40 MB free hard disk space, SVGA monitor (256 colors or more) ; CD-ROM drive
Keywords: Nursing Care -- methods; Nursing Audit -- standards